06.02 Ex vivo functional comparison of baricitinib and tofacitinib for cytokine signalling in human leukocyte subpopulations. (1st March 2017) - McInnes, Iain; Higgs, Richard; Rocha, Guilherme; Zhang, Xin; Lee, Jonathan; Wehrman, Thomas; Macias, William; Zuckerman, Steven; Taylor, Peter; Gentile, Maurizio
Abstract : Background: Baricitinib (bari) and tofacitinib (tofa) are selective JANUS kinase inhibitors (JAKi). In biochemical assays, bari exhibits greatest potency against JAK1 and JAK2, whereas that for tofa is against JAK1 and JAK3. The objective was to determine whether differences in JAKi specificity translate to differences in cellular signal transduction in leukocyte subpopulations stimulated by cytokines, indicated by inhibition of signal transducers of activator transcription (STATs) phosphorylation. Materials and methods: Peripheral blood mononuclear cells (PBMC) were obtained from healthy donors (n=6). Leukocyte preparations were incubated with JAKi using a 7 point dose range, 2.44–10, 000 nM, for 1 hour before cytokine stimulation. The half maximum inhibitory concentration (IC50 ) values were determined by plotting the mean fluorescence intensity of cytokine-stimulated and nonstimulated samples in phenotypically gated leukocyte subpopulations. 1 Results: IC50 values for bari and tofa were similar for interleukin (IL)−6 across leukocyte subsets. Differences were observed for other cytokines. The IC50 across leukocyte subpopulations stimulated with the same cytokine varied 2–3 fold per compound. The most significant differences between JAKi IC50 values were for cytokines that use JAK1/3. Tofa was a more potent inhibitor of IL-2, IL-4, IL-15, and IL-21 induced STAT phosphorylation than bari. Both compounds inhibited IL-10 stimulation of phosphorylated STAT3 (pSTAT3) and interferon (IFN)-α stimulation of pSTAT1, pSTAT3, and pSTAT5 similarly. Inhibition of IFNα pSTAT3 and pSTAT5 were similar for both JAKi, although less potent in inhibiting STAT1 phosphorylation. Bari and tofa inhibited granulocyte–macrophage colony-stimulating factor (JAK2) and granulocyte colony-stimulating factor and IFNγ signalling, with bari exhibiting a greater effect in monocytes than tofa. Conclusions: The differences in IC50 for key cytokine stimuli suggest fundamental functional differences across classes of JAKi. The potency of JAKi varied between different leukocyte subpopulations and is STAT substrate dependent. At the clinical level, therefore, these agents should not be considered biologically equivalent. A practical consequence is that determination of JAKi potency on IC50 based solely on a nongated whole blood assay would not detect differential responses of leukocyte subpopulations by JAKi. Acknowledgment: Original abstract (c) by EULAR/BMJ. First presented at 'EULAR 2016' and published in 10.1136/annrheumdis-2016-eular.1512. Any reprints, promotional options, education material etc have to be done through the original source (ARD/BMJ). Reference: 1.Krutzik, et al. Nat Methods. 2006;3(5):361–368.